KAHOOT! AS A TOOL TO GAMIFY LEARNING PROCESS AT MARITIME HIGHER EDUCATION - Diahyleva, Olena; Leshchenko, Alona; Paziak, Alla; Yurzhenko, Alona (Journal of Information Technologies in Education (ITE), 2024)
The article is devoted to the use of Kahoot! as a game-based learning platform at a higher education institution. This paper has analyzed the influence of Kahoot! on learning outcomes of future maritime professionals. The process of the “Feedback” tool use in the educational process at a higher maritime education institution is described. The article reviews the scientific literature on gamification in learning, e.g., the study of other researchers and their approaches to using the tools such as Kahoot!. The paper emphasizes the fact of limited opportunities for the Kahoot! free use despite the company’s commercial interests. The paper describes the usage of Kahoot! as an interactive tool in both synchronous and asynchronous modes. The synchronous mode enables teachers to conduct quizzes in real time, and students to take part in them using their devices, which promotes active participation and healthy competition. In asynchronous mode, teachers can assign independent study tasks to students, who can perform them with Kahoot! at their own convenience, allowing for flexibility in learning. The study presents the results of an experiment conducted at Kherson State Maritime Academy, where Kahoot! has been used in teaching Maritime English and humanities. The data analysis has identified positive changes in the level of students' professional competence, which confirms the improvement of the learning material understanding. The research analyzed the role of Kahoot! in the organization of feedback between teacher and students during classes. Its specifics and features are determined precisely as a pedagogical toolkit for quickly conducting a section of students’ acquired knowledge during any form of education and various forms of educational classes. In general, the research and implementation of novel approaches in gamification and game-based learning give access to creating an effective learning environment. Further research prospects include the study of the use of other gamification tools and game-based learning at maritime higher education institutions (e.g., Mentimeter, Miro).